PENGARUH VARIASI DIAMETER MAKSIMUM AGREGAT DALAM CAMPURAN TERHADAP KEKUATAN TEKAN BETON - Helwiyah Zain (Jurnal Teknik Sipil Unaya, 2017)
Aggregate is a natural mineral grains that serve as filler in concrete mix, and the greatest material contained in the concrete. These material influence on the properties of concrete, so that the diameter size selection is essential in making the concrete. This study aims to determine the effect of variations of aggregate maximum diameter to the compressive strength of concrete. In this study used 15 specimens, were divided into 3 groups witch each of 5 specimens. Each group is distinguished aggregate maximum diameter: 31.5 mm, 16 mm, and 8 mm. Specimens used in this study is the specimen cylinder with a diameter of 15 cm and 30 cm high. Speciment tested done at age of concrete 28 days. The average compressive strength of concrete for each group of test based on variations of  the aggregate maximum diameter is: for the aggregate maximum diameter of 31.5 mm = 249.67 kg / cm2; the aggregate maximum diameter 16 mm = 274.91 kg / cm2; and the aggregate maximum diameter of 8 mm = 326.74 kg / cm2. Based on these test results, show that the average compressive strength of the concrete for the aggregate maximum diameter of 16 mm is 10.11% stronger than the concrete with the aggregate maximum diameter of 31.5 mm; and the strength of concrete aggregate maximum diameter of 8 mm, 30.87% stronger than the concrete with aggregate maximum diameter of 31.5 mm.